A study of microparticle shape and surface chemistry effects on interactions with macrophages - Bruce, Gordon (2021)
Internalisation of nano- and microparticles, particularly by macrophages, is a fundamental process impacting the efficacy of particulate delivery systems. A greater understanding of how particle properties such as size, hydrophobicity, surface chemistry, surface charge, and shape influence this process will therefore lead to the design of more effective drug delivery systems and improved clinical outcomes. Recently, there has been a number of studies focussing on how the shape of nanoparticles affects their internalisation, however few studies focus on microparticle delivery systems which are especially useful in the field of inhaled drug delivery. This work aimed to explore the influence of microparticle shape, size, and surface chemistry in order to strengthen the knowledge in this area and assist in the design of microparticle delivery systems. In this work, microfabrication techniques have been applied to produce a range of microparticles of diverse shape in order to assess their internalisation by RAW 264.7 macrophages. Additionally, surface modification of different sized spherical particles with zwitterionic surface chemistry has been achieved to explore how these properties impact cellular internalisation. Silicon oxide microparticles of spherical, hexahedral, and truncated pyramid shapes were fluorescently labelled using covalent silane linker chemistry to allow their detection by confocal microscopy and imaging flow cytometry. Each particle shape was shown to be internalised by macrophages and to follow identical uptake pathways resulting in each particle shape residing in the phagolysosome after internalisation. Truncated pyramids were internalised by a lower percentage of macrophages than spherical particles, however in macrophages stimulated with lipopolysaccharide prior to particle administration, no differences in uptake of different shapes were observed. A wider range of microparticle shapes including hexahedrons, bars, cubes, and circular disks were microfabricated using polycrystalline silicon and a label-free method used to detect particle uptake by light scattering using imaging flow cytometry. The percentage of cells internalising particles was shown to be dependent on particle shape and in particular, differences in uptake between hexahedral and circular disk shaped particles indicate that points of high curvature may act to increase internalisation. The effect of these polycrystalline silicon microparticle shapes on cellular metabolism, membrane permeability, and release of lysosomal enzymes was then explored revealing no differences in response to different particle shapes across a range of concentrations. Spherical silicon oxide particles (diameter 0.5, 1, 3 μm) modified either with amine or zwitterionic surface chemistry were applied to cells by equivalent total mass, number, and surface area. Particle uptake was highly dependent on particle dose, dose metric, and particle size, however no difference in particle uptake was seen between the different surface chemistries studied. Additionally, uptake of particles was assessed in the presence of dipalmitoyl phosphorylcholine, a major component of lung surfactant, which resulted in reduced uptake of smaller (0.5, 1 μm) particles but had no effect on the uptake of larger (3 μm) particles.